The Effect of Azolla Compost and Inorganic Nitrogen Fertilizer on the Growth and Yield of Cucumber - Zulkurnia, Ari; Widodo; Fahrurrozi; Alnopri; Putri, Elsa Lolita; Murcitro, Bambang Gonggo (BPFP Universitas Bengkulu, 2024)
Cucumber is a popular vegetable that can be consumed fresh or processed into pickles, preserves, and other products. Efforts to enhance cucumber yield have been made through the application of Azolla compost and inorganic nitrogen (N) fertilizer. This study aimed to evaluate the interaction between different doses of Azolla compost and inorganic N fertilizer on cucumber growth and yield, as well as to determine the optimal doses of both fertilizers. The experiment was conducted from December 2021 to February 2022 in Medan Baru, Muara Bangkahulu District, Bengkulu City. A factorial randomized complete block design was employed with two factors: (1) Azolla compost doses (0 g plant-1, 90 g plant-1, 180 g plant-1, and 270 g plant-1) and (2) inorganic N fertilizer doses (0 g plant-1, 0.9 g plant-1, 1.7 g plant-1, and 2.5 g plant-1), resulting in 16 treatment combinations, each replicated three times. Data were analyzed using ANOVA at a 5% significance level, followed by Duncan’s Multiple Range Test for significant variables. Results indicated that there were no significant interaction effects between Azolla compost and inorganic N fertilizer on cucumber growth and yield. The 180 g plant-1 dose of Azolla compost produced the best results in terms of vine length, leaf number, fruit weight per plant, and plant dry weight. However, inorganic N fertilizer had no significant effect on cucumber growth and yield. Further research is needed to explore the effects of inorganic N fertilizer and the potential of Azolla as an environmentally friendly organic fertilizer in sustainable agricultural systems.